Changing the environment to promote health-enhancing physical activity. - Foster, C; Hillsdon, M (2004)
Supportive environments have been used to change and influence health behaviours like smoking. While psychological and ecological theories and models demonstrate the possible influences of the environment on health-enhancing physical activity (HEPA), little is known about the effectiveness of the environmental interventions. This paper presents the results of a systematic review of studies that used environmental interventions to increase health-enhancing physical activity. Two groups of studies were found, studies that changed the physical environment by creating new HEPA facilities, policies and supporting mechanisms, and studies that used the elements of the environment as an active or sedentary 'point of choice', via educational materials to promote stair use. Environmental change studies showed a small increase on HEPA behaviour, but the relative impact of environment changes was not evaluated. A number of before and after studies have observed a weak effect of a simple environmental change to stimulate stair climbing while travelling or shopping. Current national policy has embraced the environment as an option for promoting health-enhancing physical activity, especially active travel, in spite of the lack of effectiveness data. It is recommended that existing or planned public health environment and HEPA initiatives should use appropriate evaluation methods to assess their efficacy and effectiveness. Further developmental research into the nature of the relationship of the environment to particular HEPA behaviours is strongly recommended before developing new environmental interventions.